Dietary ingestion of magnesium and iron and their relationship with oxidative stress in obese women (Research, Society and Development, 2020)
The aim of the present study was to evaluate the relationship between magnesium and iron food intake and oxidative stress marker in obese women. It was characterized as a case-control study, involving 67 women, aged between 20 and 59 years, which were divided into two groups: control group (eutrophic women, n = 42) and case group (women with obesity, n = 25). Weight and height measurements were taken to calculate body mass index, as well as calorie, macronutrient, magnesium and iron intake. Blood samples were collected from the participants for further analysis of plasma concentrations of TBARS (Thiobarbituric Acid Reagents). Data were analyzed using the SPSS for Windows 22.0 statistical program. As results, it was observed that the mean values and standard deviations of energy intake and macronutrients found in the consumed diets did not present statistically significant difference between the groups (p> 0.05). It was also observed that the case group and the control group ingested inadequate magnesium and adequate amounts of iron, according to the reference values, with no difference between the groups. TBARS concentrations of obese women were higher when compared to the control group; however, there was no correlation between the magnesium and dietary iron parameters and TBARS in the groups. Thus, it was concluded that the intake of magnesium and iron micronutrients did not seem to influence the oxidative stress marker of the study participants.